High‐Performance Aluminum Ion Battery Using Cost‐Effective AlCl3‐Trimethylamine Hydrochloride Ionic Liquid Electrolyte. (10th May 2020) - Ng, Kok Long; Dong, Tony; Anawati, John; Azimi, Gisele
Abstract: The critical need for cost‐effective and sustainable large‐scale battery technologies for harvesting renewable energy has led to a new research wave on novel batteries made of low‐cost, high‐abundance, high‐performance, and safe components. Among the emerging candidates for post‐lithium‐ion batteries, aluminum‐based batteries are particularly promising due to the high theoretical capacities, low cost, and high abundance of raw materials. Most advanced nonaqueous rechargeable Al batteries rely on costly dialkylimidazolium chloride‐based chloroaluminate ionic liquids and this added cost inevitably diminishes various benefits of utilizing Al as the anode material. Here, a high‐performance Al battery made of Al anode, graphene nanoplatelets (GNPs) cathode, and a cost‐effective AlCl3 ‐trimethylamine hydrochloride (AlCl3 ‐TMAHCl) ionic liquid electrolyte is reported. The battery delivers a high specific capacity of 134 mAh g −1 at 2000 mA g −1 while maintaining Coulombic efficiency (CE) above 98% over 3000 cycles. Moreover, it delivers a specific capacity of 83 mAh g −1 with a CE of 97% under ultrafast charging at 4000 mA g −1 (1 min) and slow discharging at 100 mA g −1 (50 min) conditions. Considering the low cost and high performance, AlCl3 ‐TMAHCl electrolyte opens up a new avenue for the development of next‐generation Al batteries. Abstract : The aluminum‐ion battery (AIB) is a promising candidate for novel battery technologies that require low‐cost, high‐performance, and high‐safety components. To overcome cost limitations imposed by the utilization of dialkylimidazolium chloride‐based ionic liquids (ILs) in most AIB research, a cost‐effective AlCl3 ‐trimethylamine hydrochloride (TMAHCl) IL electrolyte is identified. The resulting Al/graphene nanoplatelets battery demonstrates excellent fast‐charge/slow‐discharge capability and long‐term stability over a few thousand cycles.